The Potential and Impact of the Expansion of Cattle Pastures on the Economy in Phonthong District, Luang Prabang Province - phovisay, somsay; Phasouk, Amphone; chanthakhoun, vongpasith (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study investigates the economic potential and environmental impacts of expanding cattle pastures in Phonthong District, Luang Prabang Province, Laos, located approximately 232 kilometers from the provincial capital. Cattle farming has been identified as a strategic livelihood development priority for the district. The research aims to assess both the benefits and challenges associated with pasture expansion. A mixed-methods approach was used, collecting data from 142 cattle-raising households in four villages Na Son, Na Luang, Pung Hon, and Pak Eum through structured interviews and attitude scoring. Descriptive statistics were employed for analysis, and group differences were examined using one-way ANOVA at a 95% confidence level. Findings revealed a high overall perception of cattle farming potential (mean = 4.27). Market potential was rated highest (4.60), followed by economic benefits (4.41), policy and geographic conditions (4.20), and knowledge and capability (3.92). Perceived environmental impacts were generally low (mean = 1.67), with slightly higher concerns about land and forest areas (mean = 1.91). Demographic variables such as gender, age, education, marital status, occupation, family size, labor force, and herd size showed no significant differences in perception. However, differences were found among villages. Pung Hon rated the highest potential (mean = 4.57), followed by Na Son (4.20), Na Luang (4.19), and Pak Eum (4.14). Perceptions of environmental impact varied significantly by herd size: small-scale farmers (1–5 cattle) reported "very low" impacts (mean = 1.47), while large-scale farmers (40+ cattle) reported "moderate" impacts (mean = 2.66) (p < 0.05). The study concludes that cattle expansion strategies should be tailored to each village’s conditions, with environmental management focused on large-scale operations. The findings provide valuable guidance for creating policies that support sustainable economic growth in Phonthong’s cattle industry.